Atomistic simulation of soldering iron filled carbon nanotubes - Munizaga, Vicente (2014)
The melting and soldering processes of two iron filled carbon nanotubes is explored by means of classical molecular dynamics, in order to develop an understanding of the underlying mechanisms that govern the dynamics of nano-soldering. Molten Fe flows from the open end of the two CNTs, leading to a liquid junction, and eventually to a solid contact. This soldering process is accompanied by partial or total healing of the carbon nanotubes, which after cooling and relaxation form just a single unit which encapsulates the iron, depending on the relative separation, diameters and axial offset of the nanotubes. This makes for a promising scenario for CNT soldering, repairing and healing, and a variety of different tools in the field of nanoelectronics.